Analysis of Science Literacy and Chemical Literacy Content on Green Chemistry Materials in Chemistry Textbooks Class X High School in Palangka Raya City - Manik, Angel (Chemistry in Education, 2024)
The continuous advancement of science and technology requires 21st-century education to equip students with literacy skills. PISA results show that students' literacy skills in Indonesia are still relatively low. One of the factors influencing students' literacy skills and directly affecting the learning process is the availability of textbooks. Therefore, textbooks that can enhance students' literacy skills are needed. This study aims to examine the presence of scientific literacy and chemical literacy indicators in grade X chemistry textbooks on green chemistry material. This study uses a descriptive method with a quantitative approach. The sample consists of grade X chemistry textbooks that are most commonly used in SMA Negeri Palangka Raya for green chemistry material in the Merdeka Curriculum. The research instrument used is an identification sheet containing a table for analyzing scientific literacy and chemical literacy indicators. The results of this study show that the presence of scientific literacy indicators in both textbooks is nearly balanced. The analysis of both books revealed the average occurrence in each category: scientific knowledge (37.96%), science as a way of investigating (22.11%), science as a way of thinking (19.05%), and the interaction of science, technology, and society (20.88%). However, the presence of chemical literacy indicators in both textbooks is still uneven, with an unbalanced proportion. The analysis showed the average occurrence for each aspect: content (47.18%), context (14.10%), competence (13.69%), and attitude (25.03%).